Disentangling the effects of plea discount and potential trial sentence on decisions to plead guilty. (31st August 2019) - Schneider, Ryan A.; Zottoli, Tina M.
Abstract : Background: Most criminal convictions are a result of guilty pleas. Concerns have been raised that large differentials between plea and potential trial sentences can be coercive to some defendants, especially when the threat of potential trial sentence is very large. The limited research, to date, suggests that the likelihood of pleading guilty goes up with increasing size of potential trial sentence. However, existing studies have failed to separate the effects of trial sentence and plea discount; as a result, in almost all studies, large potential trial sentences are paired with large discounts and small trial sentences with small discounts, making it difficult to know how the threat of trial sentence actually affects defendant decisions. Method: In this study, we examined the effects of guilt, magnitude of potential trial sentence (5 years and 25 years), and size of plea discount (20%, 50%, and 75%) in a fully crossed, between‐subjects design, with acceptance of plea offer as the dependent variable. Results: We found that potential trial sentence and plea discount had independent and opposite effects on plea decisions, with discount carrying the most weight. Specifically, participants accepted more plea offers in higher relative to lower discount conditions and when potential trial sentence was 5 years rather than 25 years. The pattern of effects was similar for participants in guilty and innocent conditions. Implications: Our results run somewhat counter to conventional wisdom on how discount and potential trial sentence affect plea decisions and suggest that, given similar discounts, the likelihood for pleading guilty may be higher for defendants facing less serious charges that carry less severe sentences. We discuss the policy and research implications of these data.